Elementary, My Dear Watson—The Era of Natural Language Processing in Transplantation. Issue 3 (25th January 2017) - Ho, B.; Skaro, A.; Montag, S.; Zhao, L.
Abstract : A novel pilot study by Srinivas et al (page 671 ) demonstrates the feasibility of automated data extraction from unstructured data within electronic health records, which may enhance available data for model building to predict graft loss following kidney transplantation.